Peran Biro Organisasi Setda Provinsi Sumatera Barat dalam Pembinaan Pelayanan Publik Berbasis Ramah Kelompok Rentan - Annisa Noviyani; Zikri Alhadi (YASIN, 2026)
Public service is a primary responsibility of the government in ensuring the fulfillment of the public’s right to services that are equitable, accessible, and nondiscriminatory, including for persons with disabilities, older adults, pregnant women, children, and individuals with specific limitations. Although various regulations concerning public services responsive to vulnerable groups have been established, the implementation of these service standards among regional government agencies continues to show varying levels of achievement. This study aims to analyze the role of the Organization Bureau of the Regional Secretariat of West Sumatra Province in guiding the implementation of public service standards responsive to vulnerable groups among regional government agencies and to identify the constraints encountered in the guidance process. This study employed a qualitative approach with a descriptive method. Data were obtained through in-depth interviews, observations, and documentation studies involving officials of the Organization Bureau, regional government agencies, service users, and public service experts. The data were analyzed through the stages of reduction, presentation, and conclusion drawing. The results showed that the Organization Bureau performed a regulatory role through the formulation of public service guidelines and policies, a facilitative role through outreach, training, and assistance for regional government agencies, and a catalytic role through monitoring, evaluation, and the provision of recommendations for service improvement. However, the implementation of guidance has not been optimal because of budget constraints, unequal availability of service facilities and infrastructure, differences in readiness among regional government agencies, and the limited competence of personnel in serving vulnerable groups. This study concludes that optimizing inclusive and equitable public services requires strengthening the guidance function, improving personnel capacity, ensuring the equitable provision of facilities and infrastructure, and maintaining continuous coordination among regional government agencies. These findings contribute to the development of inclusive public service governance while providing a practical basis for local governments to improve the quality of services for vulnerable groups.